Katalizatory miedziowo-złotowe oparte na nośnikach typu SBA-3 – właściwości fizykochemiczne i katalityczne - Florek, Justyna (My University, 2012)
Celem prowadzonych badań było otrzymanie katalizatorów zawierających miedź i/lub złoto osadzone na nośniku SBA-3 (SBA-3, AlSBA-3, NbSBA-3); określenie wpływu różnych form miedzi i złota na teksturę i strukturę otrzymanych katalizatorów oraz na ich właściwości powierzchniowe i katalityczne. Wnioski z przeprowadzonych badań: 1. W zależności od składu chemicznego nośnika naniesiona miedź występuje w różnych formach i wykazuje różne właściwości katalityczne. 2. Źródło miedzi wywiera istotny wpływ na właściwości kwasowo-zasadowe i redoksowe modyfikowanych materiałów. 3. Dla utleniającej dehydrogenacji alkoholi najatrakcyjniejszym nośnikiem dla miedzi jest NbSBA-3. 4. Wprowadzenie złota z kwasu chlorozłotowego generuje kwasowość, która jest zależna od sposobu wprowadzenia złota. 5. Złoto wprowadzone posyntezowo na nośnik NbSBA-3-64 (Co) wykazuje inne właściwości katalityczne niż naniesione na nośnik SBA-3. 6. W zależności od składu chemicznego nośnika miedź i złoto zajmują różne pozycje na powierzchni nośnika, co determinuje właściwości katalityczne materiału. 7. Sposób otrzymania materiałów bimetalicznych ma wpływ na ich aktywność katalityczną. 8. Wprowadzenie złota i miedzi na nośnik NbSBA-3-64 (Co) powoduje znaczny wzrost aktywności katalitycznej i wydajności produktów procesu selektywnego utleniania metanolu. 9. Stosując odpowiednie kombinacje składu chemicznego wielometalicznych kontaktów oraz metod nanoszenia faz aktywnych można zaplanować katalizatory wykazujące selektywność do żądanego produktu w procesie utleniania metanolu.

The aim of the study was to obtain catalysts containing copper and/or gold particles embedded on SBA-3 support (SBA-3, AlSBA-3, NbSBA-3), to determine the effect of different forms of copper and gold on the texture and structure of the obtained catalysts and their surface properties and catalytic activity.The conclusions of the study: 1. Depending on the chemical composition of the support copper occurs in different forms and has different catalytic properties. 2. The source of copper has a significant influence on the acid-base and redox properties of modified materials. 3. For the oxidative dehydrogenation of alcohols the most attractive media for copper is NbSBA-3. 4. Acidity of modified gold materials is dependent on the procedure of introduction of gold. 5. Gold introduced to the NbSBA-3-64 (Co) support has a different catalytic properties than those deposited on SBA-3 material. 6. Depending on the chemical composition of support copper and gold particles occupy different positions on the carrier surface, which determines the catalytic properties of the material. 7. The modification procedure used to obtain bimetallic materials affects their catalytic activity. 8. The introduction of gold and copper on the NbSBA-3-64 (Co) support results in significant increase in the catalytic activity of the materials received. At a temperature of 523 K the Cu/Au/NbSBA-3-64 (Co-N) materials are the most active catalysts in process of selective oxidation of methanol and characterized by high selectivity to partial oxidation products of alcohol. 9. By using appropriate combinations of chemical composition of trimetallic contacts and methods of application can be scheduled phase active catalysts showing selectivity for the desired product in the oxidation of methanol.
Mesoporous materials of SBA-3 type modified with gold and copper– physico-chemical properties and catalytic activity
Wydział Chemii: Zakład Katalizy Heterogenicznej
Keywords: złoto; gold; miedź; copper; nośniki sba-3; SBA-3 mesoporous materials; utlenianie metanolu; oxidation of methanol; materiały bimetaliczne; bimetallic materials